On the failure of silicone breast implants: New insights by mapping the mechanical properties of implant shells - Schubert, Dirk W.; Kaschta, Joachim; Horch, Raymund E.; Walter, Bastian; Daenicke, Jonas (Polymer International, 2014)
This review summarizes the knowledge on rupture (in vivo as well as under laboratory conditions) of gel-filled silicone breast implants, which has been an open question since the first implantation in 1962. We present recent progress which has been made by a mapping of the mechanical properties of the shell material together with a statistical failure analysis by means of a Weibull fit. Reference implants and intact as well as ruptured explants are tested after several years in vivo using tensile tests. Up to 110 dumbbell-shaped specimens per implant are measured allowing a detailed mapping of the mechanical properties of the silicone shell. Therefore, it is possible to illustrate the results of the tensile tests by mapping the measured values of the implants in the form of a contour plot revealing novel insights. The contour plots clearly display that the mechanical behaviour (e.g. stress at break) varies significantly over the shell. Additionally, a map is proposed which clearly shows separated clusters for different manufacturers and product categories. © 2013 Society of Chemical Industry
UnivIS-Import:2015-03-09:Pub.2013.tech.FT.FT-TM.onthef